2019
DOI: 10.18535/ijmsci/v6i5.06
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of PD-L1 and CD133 Expression with Metastasis in Invasive Breast Carcinoma of Luminal B Subtype

Abstract: Background: Breast carcinoma is a cancer with the highest number in women, Luminal B is the highest number of all types of invasive breast carcinoma in the world.  Invasive  breast carcinoma of luminal B is breast carcinoma with hormone-receptor positive (estrogen-receptor and/or progesterone-receptor positive), and either HER2 positive or HER2 negative with high levels of Ki-67. Determining the aggressiveness factor in  invasive breast carcinoma is very important. PD-L1 is a checkpoint in the cancer cell immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
2
1
1
Order By: Relevance
“…However the comparison was not statistically significant. A trend of higher incidence of CD133 expression was noted with advanced histology grade which was consistent with result obtained in other studies (Anwar et al, 2019;Liou et al, 2019;Han, 2015). This may be due to availability of less number of cases in our study when compared with other studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However the comparison was not statistically significant. A trend of higher incidence of CD133 expression was noted with advanced histology grade which was consistent with result obtained in other studies (Anwar et al, 2019;Liou et al, 2019;Han, 2015). This may be due to availability of less number of cases in our study when compared with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…However the findings did not reach any statistical significance. The present study showed highest number of cases belonging to T2 i.e 23 cases (40.35%) which correlated with other studies (Anwar, 2019). In present study there was no correlation between the tumor size and the CD 133 expression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Immune evasion is a hallmark feature, as evidenced in various malignancies. CD47 and PD-L1 are recognized to play a critical role in cancer cells evading cytotoxic T cell assaults, which results in uncontrolled tumor development during the early stages of invasion and metastasis [ 36 , 16 ]. Our findings indicated increased CD47 expression in metastatic HGSC tumor cells compared to non-metastatic HGSC tumor cells.…”
Section: Discussionmentioning
confidence: 99%